Improving the Property–Function Tuning Range of Thiophene Materials via Facile Synthesis of Oligo/Polythiophene‐S‐Oxides and Mixed Oligo/Polythiophene‐S‐Oxides/Oligo/Polythiophene‐S, S‐Dioxides. (22nd August 2016) - Di Maria, Francesca; Zangoli, Mattia; Palamá, Ilaria Elena; Fabiano, Eduardo; Zanelli, Alberto; Monari, Magda; Perinot, Andrea; Caironi, Mario; Maiorano, Vincenzo; Maggiore, Antonio; Pugliese, Marco; Salatelli, Elisabetta; et al.
Abstract : A platform is described for the first time for the facile synthesis of oligo‐ and polythiophene‐S‐oxides and the corresponding ‐S, S‐dioxides in short times, mild conditions, high yields. Employing ultrasound assistance, brominated thiophenes are selectively mono‐ or dioxygenated at room temperature. These building blocks are then combined with metalated thiophenes via microwave‐assisted cross‐coupling reactions through a "Lego‐like" strategy to afford unprecedented oligo/polythiophene‐S‐oxides and mixed ‐S‐oxides/‐S, S‐dioxides. It is demonstrated that depending on the number, type, and sequence alternation of nonoxygenated, monooxygenated, and dioxygenated thiophene units a very wide property–function tuning can be achieved spanning from frontier orbital energies and energy gaps, to charge transport characteristics and supramolecular H‐bonding interactions with specific proteins inside live cells. Abstract : A platform is described for ultrasound‐assisted synthesis of oligo‐ and polythiophene‐S‐oxides and ‐S, S‐dioxides in short reaction times, mild conditions, and high yields. By changing the number and sequence alternation of nonoxygenated, monooxygenated, and dioxygenated thiophene units a very wide tuning of frontier orbital energies, charge transport characteristics, and supramolecular H‐bondings to specific intracellular proteins is achieved.